Analysis of functional response in presence of schooling phenomena: An IBM approach. (May 2015) - Accolla, Chiara; Nerini, David; Maury, Olivier; Poggiale, Jean-Christophe
Highlights: Functional responses emerge from an IBM in which schooling occurs. Collective behaviour of prey causes higher functional responses. Holling type II functional response emerges when prey aggregation does not occur. Holling type III functional response emerges if prey aggregate. Abstract: The aim of this paper is to analyse the emergence of functional response of a predator–prey system starting from diverse simulations of an Individual-Based Model of schooling fish. Individual characteristics can, indeed, play an important role in establishing group dynamics. The central question we address is whether or not aggregation influences predator–prey relationships. To answer this question, we analyse the consequences of schooling when estimating functional response in four configurations: (1) no schooling of either prey nor predators; (2) schooling of prey only; (3) schooling of predators only; and (4) schooling of both prey and predators. Aggregation is modelled using the rules of attraction, alignment and repulsion. We find important differences between the various configurations, highlighting that functional response is largely affected by collective behaviour. In particular, we show: (1) an increased predation efficiency when prey school and (2) different functional response shapes: Holling type II emerges if prey do not school, while Holling type III emerges when prey aggregate.